Different cooling strategies applied during inter-set rest intervals in high-intensity resistance training - Esteves, G. J.; Garcia, R. A.; Azevedo, P. H. S. M. (International Journal of Exercise Science, 2021)
The purpose of this study was to verify whether cooling between sets during high-intensity resistance exercise improves physical performance and to compare performance among different sites of cooling. It is important because delaying the muscular fatigue could improve total volume at a training session which could lead to greater hypertrophy. Nine healthy and recreational resistance training experienced men, performed six tests of a biceps curl exercise on different days. The first test was the one-repetition maximum test (1RM). Following, we applied five sessions, in crossover and randomized (counter-balanced) design. The subjects received different cooling strategies in each session for 1-min (inter-set rest interval): Control (C) (no Cooling); Palm Cooling (PC); Neck Cooling (NC); Local Cooling (LC) or Tunnel Temperature Cooling (TTC). We analyzed the maximum number of repetitions and the rating of perceived exertion (RPE). The Bayesian analysis showed that no cooling strategy was able to improve performance compared to control, and just NC, when compared to control, showed a 71% probability of increasing the total volume of repetitions. Also, RPE was not modulated by any cooling strategy compared to control, but NC has a chance to reduce individuals' RPE by 52%. In conclusion, no cooling strategy was efficient to improve physical performance during a high-intensity resistance exercise.